How collective violence emerges and escalates - Adang, Otto (Public Order Policing, 2024)
The chapter links theory and practice of public order management. Based on systematic observations of mass events where violence occurred (or was feared), an evidence-based model for the initiation and escalation of collective violence is presented. Based on this model, strategic principles for the police management of mass events are described, which are already successfully applied in several countries.